Associação entre obesidade e condição periodontal: análise epidemiológica e microbiológica em indivíduos obesos, candidatos e submetidos à cirurgia bariátrica - Andre Luiz Pataro (2010)
Obesity is a chronic and multifactorial disease, considered a major public health concern worldwide. Rencently, obesity has been associated to the susceptibility and severity of periodontal disease. However, studies about the influence of morbid obesity on periodontal diasease and periodontal pathogens in mouth and stomach are still scarce. Therefore, 722 elegible individuals were included on the studies: 370 individuals at surgical obesity treatment from a reference surgical center of Belo Horizonte, Minas Gerais, Brazil and 352 individuals accompanying these patients. Out of this population, 594 women made up the case-control sample; 345 individuals made up the cross-sectional study sample which focused on pre and post bariatric surgery; and 154 individuals were selected for a microbiological assay. In the 3 studies, the individuals were periodontally examined. Biological, demographic and behavioral risk variables linking obesity and periodontal disease were also evaluated. Periodontitis was defined as at least 4 teeth with one or more sites showing simultaneously probing depth (PD) 4 mm and clinical attachment level (CAL) 3 mm. The frequencies of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Parvimonas micra, Treponema denticola, Tannerella forsythia, Campylobacter rectus e Helicobacter pylori were determined by PCR (Polymerase Chain Reaction) from dorsum of tongue, saliva and stomach biopsies samples from 49 individuals. Descriptive and comparative analysis of risk associated variables and microbial frequencies were performed. Univariate and multivariate analysis were conducted when appropriate. A high prevalence of periodontal disease was verified among individuals with different degrees of obesity, especially on those presenting morbid obesity [Body Mass Index (BMI) 35 kg/m2]. This group showed significant statistical differences when compared to normal weight individuals (<0,05). In the group of females with BMI 30 kg/m2, was verified that smoking (OR=3,51; IC 95%=1,34-5,82), diabetes (OR=2,86; IC 95%=1,92-5,51) and hypertension (OR=2,65; IC 95%=1,32-3,65) were variables positively associated with periodontitis. Bariatric surgery resulted on a worst periodontal status 6 months after the procedure. However, individuals analyzed in postoperative periods longer than 6 months revealed better periodontal status, probably reflected by systemic health improvement. Periodontitis was positively and incrementally associated to different obesity levels. The highest frequencies of P. gingivallis, T. forsythia, T. denticola and C. rectus were on saliva of postoperative individuals with periodontitis. Periodontal pathogens were also detected in stomach biopsies in high frequencies at pre (until 91,6%) as post surgical periods (until 83,3%). High occurrence of H. pylori was verified in mouth and in stomach, as expected. Bariatric surgery seems to influence periodontal homeostasy, as well as a higher occurrence of periodontal pathogens in stomach and mouth. These 3 studies strongly indicated the need for early periodontal diagnosis and inclusion of periodontal care in health care programs for the obese, especially on those providing surgical treatments for obesity.